2020
DOI: 10.1007/s11274-020-02947-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of volatile organic compounds by Aureobasidium species against gray mold of tomato and table grape

Abstract: Aureobasidium strains isolated from diverse unconventional environments belonging to the species A. pullulans, A. melanogenum, and A. subglaciale were evaluated for Volatile Organic Compounds (VOCs) production as a part of their modes of action against Botrytis cinerea of tomato and table grape. By in vitro assay, VOCs generated by the antagonists belonging to the species A. subglaciale showed the highest inhibition percentage of the pathogen mycelial growth (65.4%). In vivo tests were conducted with tomatoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…For example, our study is supported by past results on Hanseniaspora uvarum, which was shown to be an effective BCA in, e.g., controlling fungal rot in strawberries by biofumigation using VOCs [64]. It reduces the natural development of decay in grapes and strawberries and maintains quality parameters [28,57,65,66]. It also exerts biocontrol against chili fruit rot [67] and green mold of postharvest oranges [68]; and inhibits the growth of B. cinerea with multiple modes of action, including competition for nutrients and space, host defense induction, morphology change and secondary metabolites [57,65,66,69,70].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…For example, our study is supported by past results on Hanseniaspora uvarum, which was shown to be an effective BCA in, e.g., controlling fungal rot in strawberries by biofumigation using VOCs [64]. It reduces the natural development of decay in grapes and strawberries and maintains quality parameters [28,57,65,66]. It also exerts biocontrol against chili fruit rot [67] and green mold of postharvest oranges [68]; and inhibits the growth of B. cinerea with multiple modes of action, including competition for nutrients and space, host defense induction, morphology change and secondary metabolites [57,65,66,69,70].…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, 2-phenylethanol isolated from K. apiculata showed inhibitory activity against green and blue mold in citrus fruits caused by P. digitatum and P. italicum [19]. It was also shown to play a critical role in the antagonistic activity of A. pullulans against postharvest fruit pathogens both in vitro and in vivo [56,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They could be considered as ideal antimicrobials since no physical interaction between the biocontrol agent and the food or pathogen is necessary. Antagonistic yeasts of the genus Hanseniaspora [ 112 ] and A. pullulans [ 113 ] showed inhibition efficacy against B. cinerea by producing VOCs. Similarly, killer toxins can also control post-harvest pathogens [ 35 ].…”
Section: Yeasts As Biocontrol Against Fungal Pathogenic Microorganismsmentioning
confidence: 99%
“…The species A. pullulans is also known as an effective biocontrol agent that is thought to employ a range of mechanisms to suppress the growth of other microorganisms [9]. These mechanisms include direct competition [15][16][17], the secretion of enzymes and secondary metabolites [4-8, 18, 19], the production of volatile compounds [20][21][22][23][24][25], as well as the induction of resistance in crop plants [26,27]. Many Aureobasidium isolates show strong biocontrol activity against destructive plant diseases such as moulds, rots and blights [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%